The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1129-2377-14-54
|View full text |Cite
|
Sign up to set email alerts
|

Primary headaches, attention deficit disorder and learning disabilities in children and adolescents

Abstract: BackgroundPrimary headaches and Learning difficulties are both common in the pediatric population. The goal of our study was to assess the prevalence of learning disabilities and attention deficit disorder in children and adolescents with migraine and tension type headaches.MethodsRetrospective review of medical records of children and adolescents who presented with headache to the outpatient pediatric neurology clinics of Bnai-Zion Medical Center and Meyer Children’s Hospital, Haifa, during the years 2009–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 33 publications
4
36
1
1
Order By: Relevance
“…This study confirms most literature studies on the possible relationship between headache and ADHD, especially concerning the important impact on quality of life and academic performance [ 1 3 ]. It confirms the remarkable role of ADHD traits in the personal and family history of the juvenile patients affected by primary headaches.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study confirms most literature studies on the possible relationship between headache and ADHD, especially concerning the important impact on quality of life and academic performance [ 1 3 ]. It confirms the remarkable role of ADHD traits in the personal and family history of the juvenile patients affected by primary headaches.…”
Section: Discussionsupporting
confidence: 90%
“…Attention deficit and hyperactivity disorder (ADHD) and headache are two very common diseases in childhood and both of them have an important impact on quality of life and academic performance [ 1 ]. In the literature there are many studies on psychopathology in headache, but the relationship between headache and ADHD is considered in few of them [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both the diseases often become disabling for children and families and are accompanied by poor academic performance [1,2], low cognitive and emotional functioning [3][4][5][6], and wrong sleep habits [7,8], leading to severe impairments of the child's quality of life [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Strine et al [23] evidenced an odds ratio of 2.6 to have inattention and hyperactivity in children who referred headache, and Genizi et al showed that learning disabilities and ADHD are more common in children and adolescents who are referred for neurological assessment for primary headaches than those described in the general pediatric population [1], while Arruda et al demonstrated that migraine and TTH are not comorbid to ADHD overall but are comorbid to hyperactive-impulsive behavior [20].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that patients with migraine [9][10][11] or tension-type headache [11] often display various attention problems.…”
Section: Introductionmentioning
confidence: 99%